Bay Leaf Brewing Lowers Blood Sugar Levels in Elderly People with Type 2 Diabetes Mellitus - Ni Nyoman Ayu Satriawati; I Gusti Ketut Gede Ngurah; I Wayan Suardana; Ketut Sudiantara; I Ketut Gama; Komang Ayu Henny Achjar; Wayan Mustika; Agus Sri Lestari (Health Dynamics, 2025)
Background: Type 2 diabetes mellitus in the elderly can cause increased blood sugar levels that risk damaging various body systems. One natural alternative to help lower blood sugar levels is to utilize bay leaves, which are known to have active ingredients that have the potential to be antidiabetic. This study aims to determine the effect of boiled bay leaves on blood sugar levels in elderly people with type 2 diabetes mellitus. Methods: The study used a pre-experimental design with a one group pre and post test design approach. The study population was elderly people with type 2 diabetes mellitus in the Abang II Health Center, Karangasem, Bali Province, Indonesia with a sample size of 49 people selected using the proportional stratified random sampling technique. Respondents were given an intervention in the form of consuming 220 ml of boiled bay leaf water every morning before eating for seven consecutive days. The bay leaves used were old leaves weighing 2 grams. Blood sugar levels were measured using the Easy Touch tool, with established standard procedures. Results: The results showed that before the intervention, all respondents had random blood sugar levels >200 mg/dL. After the intervention, 93.9% of respondents experienced a decrease in blood sugar levels to <200 mg/dL. The paired t-test statistical test showed a p value = 0.001 (p <0.05), which means there was a statistically significant decrease in blood sugar levels. Conclusions: The conclusion of this study is that boiled bay leaf water is effective in lowering blood sugar levels in elderly people with type 2 diabetes. It is recommended to use it as a safe and natural additional therapy, while continuing to consult a doctor for further monitoring.